Recent advances in catalytic reduction of CO2 through bismuth based MOFs - Rabia Zafar; Ayesha Javaid; Muhammad Imran; Shoomaila Latif; Muhammad Naeem Khan; Liviu Mitu; Romică Crețu (Journal of Saudi Chemical Society, 2024)
Bismuth based MOFs have appealed much curiosity in different catalytic processes due to their remarkable properties, which include their porous structure, less toxicity, abundance and high specific surface area. With their distributed active sites and constrained reaction regions, Bi based MOFs have a bright future as catalysts for extremely focused CO2 reduction by electrocatalysis reactions (ECO2RR). Formic acid (HCOOH), one of the byproducts of these processes, is notable because of its high economic worth. An extensive summary of Bi-MOFs and their derivatives used in ECO2RR and the photocatalytic reduction of CO2 into useful compounds is given in this review. Bi-MOFs synthesis methods for both electro and photocatalyst applications are discussed, along with an analysis of their unique benefits. Interestingly, a variety of Bi-MOFs and related offshoots are highlighted, including bimetallic catalysts and Bi-based MOF-derived nanocomposites. Bi-MOFs catalysts’ catalytic efficacy is demonstrated to be closely related to the MOF structure blocks-metal ions and organic linkers as well as particular circumstances controlling their derivatization. As a result, Bi-MOFs catalysts have a wide range of functions and provide the possibility of controlling the catalytic performance. This review describes the current obstacles in this area and makes recommendations for future research paths to advance the use of Bi-MOFs as electro- and photocatalysts.